2012
DOI: 10.1038/jid.2012.198
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Alcohol May Modify the Risk for Non-Melanoma Skin Cancer: Results of a Large Danish Prospective Cohort Study

Abstract: Alcohol has not been linked definitively to non-melanoma skin cancer. We examined whether alcohol intake affects the risks for basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) using data on 54,766 persons enrolled in the prospective Diet, Cancer, and Health cohort. Statistical analyses were based on the Cox proportional hazards model. All hazard ratios (HRs) were multivariate adjusted. Adjustment for exposure to UVR was not possible, but all analyses were adjusted for factors related to susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 22 publications
7
41
1
3
Order By: Relevance
“…In accordance with three large cohort studies (Fung et al , 2002; Freedman et al , 2003; Jensen et al , 2012), we observed an elevated BCC risk in alcohol drinkers. Several mechanisms have been suggested to explain how alcohol may initiate and promote skin carcinogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with three large cohort studies (Fung et al , 2002; Freedman et al , 2003; Jensen et al , 2012), we observed an elevated BCC risk in alcohol drinkers. Several mechanisms have been suggested to explain how alcohol may initiate and promote skin carcinogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Although Jensen et al [16] did not find an association between risk of basal cell carcinoma and squamous cell carcinoma and overall alcohol intake in a cohort of Danish men and women, they did find an increasing hazard for BCC for wine consumption and liquor consumption. This is similar to our finding of an increased risk for NMSC for liquor and white wine preference compared to non-drinkers.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, given that the development of skin cancer depends on both sun exposure and constitutional factors, it is possible that sun exposure may interact with host risk profile to alter an individual's skin cancer risk. More recent studies also revealed that lifestyle-related factors, such as artificial tanning bed use (17-19), weight change (20,21), smoking (22,23), alcohol intake (24,25), physical activity (26,27), and rotating nights shifts (28), may also modify risks of different skin cancers. Currently a comprehensive assessment is lacking for the relationships between chronic sun exposure based on residential history, as well as sun exposure in early life, and risk of different types of skin cancer.…”
mentioning
confidence: 99%